External fixation versus internal fixation for closed unstable intra-articular fracture of the distal radius. Early results from a prospective study - Zakaria@Mohamad, Zamzuri; M, Yusof; MY, Hyzan (Malaysian Medical Associations, 2004)
This is a prospective study of a series of 26 patients with closed unstable comminuted intra-articular fracture distal end of the radius treated with two different methods of treatment to compare their anatomical and functional results. The external fixation group consisted of 12 patients and internal fixation group consisted of 14 patients. The anatomical and functional assessments were performed at six months and one year. The anatomical results at six months and one year showed that the internal fixation group was effective in maintaining the reduction compared to the external fixation group. The radial height, volar tilt and radial inclination were well maintained. However, the functional results at six months and one year showed no differences between these two types of fixation. The complication rate was higher in external fixation group. Key Words : External Fixation, Internal